PERBANDINGAN SISTEM KETATANEGARAAN PERSEPEKTIF PENERAPAN HUKUM INDONESIA DAN SINGAPURA - Desta Lia; Hendra Irawan (Siyasah Jurnal Hukum Tatanegara, 2022)
state administrative system is a matter related to the state in terms of the structure, position and composition of state institutions with regard to their duties and functions and even their authority which aims to maintain the stability of the state itself. similarities or differences in one country and even many countries, because each country has its own form of government. Here the researcher compares two countries, namely Indonesia and Singapore with this research method using Library Research. As a result, the Indonesian state has similarities in the form of government, namely a republic, besides that it also has similarities in the party system, namely multi-party while the difference is in the Indonesian presidential system of government while Singapore is presidential. Not only that, Indonesia, Singapore, has three powers, namely the executive, legislative and judiciary, but the institutions within it are different.